'Tell me exactly what's happened': When linguistic choices affect the efficiency of emergency calls for cardiac arrest. (August 2017) - Riou, Marine; Ball, Stephen; Williams, Teresa A.; Whiteside, Austin; O'Halloran, Kay L.; Bray, Janet; Perkins, Gavin D.; Smith, Karen; Cameron, Peter; Fatovich, Daniel M.; Inoue, Madoka; Bailey, Paul; et al.
Abstract: Background: Clear and efficient communication between emergency caller and call-taker is crucial to timely ambulance dispatch. We aimed to explore the impact of linguistic variation in the delivery of the prompt " okay, tell me exactly what happened " on the way callers describe the emergency in the Medical Priority Dispatch System ® . Methods: We analysed 188 emergency calls for cases of paramedic-confirmed out-of-hospital cardiac arrest. We investigated the linguistic features of the prompt " okay, tell me exactly what happened " in relation to the format (report vs. narrative) of the caller's response. In addition, we compared calls with report vs. narrative responses in the length of response and time to dispatch. Results: Callers were more likely to respond with a report format when call-takers used the present perfect (" what's happened ") rather than the simple past (" what happened ") (Adjusted Odds Ratio [AOR] 4.07; 95% Confidence Interval [95%CI] 2.05–8.28, p < 0.001). Reports were significantly shorter than narrative responses (9 s vs. 18 s, p < 0.001), and were associated with less time to dispatch (50 s vs. 58s, p = 0.002). Conclusion: These results suggest that linguistic variations in the way the scripted sentences of a protocol are delivered can have an impact on the efficiency with which call-takers process emergency calls. A better understanding of interactional dynamics between caller and call-taker may translate into improvements of dispatch performance.